A general strategy to spiro[4.n]alk-2-ene-1,6-diones and spiro[5.n]alk- 2-ene-1,7-diones via intramolecular acylation of α-sulfinyl carbanions - Manat Pohmakotr (2018)
A convenient and general synthetic method for spiro[4.n]alk-2-ene-1,6- diones and spiro[5.n]alk-2-ene-1,7-diones, which involves the intramolecular acylation of an α-sulfinyl carbanion, is described.